2005
DOI: 10.2355/isijinternational.45.1515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Operation Condition and Casting Strategy on Drainage Efficiency of the Blast Furnace Hearth

Abstract: A mathematical model is developed to quantify the effect of operation conditions and casting strategy on residual amount of slag and metal in hearth. The model is validated by a physical scale model experiment. Calculated results show that the residual amount of slag increases in proportion to the square of production. The effect of hearth permeability on the residual amount of slag is larger than slag viscosity. Then high permeability is necessary under high productivity operation condition. Although a load i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 3 publications
0
32
0
3
Order By: Relevance
“…An efficient and strictly controlled tapping is necessary for guaranteeing a stable operation and high productivity of the BF. Many recent investigations [1][2][3][4][5][6][7][8][9] on this subject have revealed that the pressure drop caused by fluid flow through the deadman in the hearth is a significant factor governing hearth drainage. However, due to the hostile environment, the possibilities to directly measure internal variables are practically nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…An efficient and strictly controlled tapping is necessary for guaranteeing a stable operation and high productivity of the BF. Many recent investigations [1][2][3][4][5][6][7][8][9] on this subject have revealed that the pressure drop caused by fluid flow through the deadman in the hearth is a significant factor governing hearth drainage. However, due to the hostile environment, the possibilities to directly measure internal variables are practically nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the experimental system is equivalent to the case where the coke-free zone extends above the taphole level, which can be caused by excessively high liquid levels in the BF hearth. 5,6) Even though a coke bed in the hearth could have an influence on the flow patterns in the taphole, it would be almost impossible to consider the effect in an appropriate way since the exact configuration of the coke particles next to the taphole is unknown.…”
Section: Model Validation On Water-oil Datamentioning
confidence: 99%
“…It has been reported that the taphole diameter (or taphole expansion rate during tapping) can significantly influence the slag residual ratio and casting duration. [5][6][7][8] Also, steeper taphole inclination could lead to higher productivity and longer casting duration since more iron can be drained out below the taphole level. However, the effect of taphole diameter and inclination angle on the taphole flow patterns has, to the best of our knowledge, not been reported.…”
Section: Theoretical Analysis Of Slag and Iron Flow Pat-mentioning
confidence: 99%
See 1 more Smart Citation
“…In the early, researchers [27][28][29]32,[35][36][37][38][39][40] supposed the dead-man was cylinder or hemisphere, owed uniform voidage, and filled the hearth along the radial. The simulation results 29,32) revealed the volume of free coke in the hearth significantly affect the line erosion, the narrower the space, the faster the metal flow, the heavier the erosion.…”
Section: Porous Medium Modelmentioning
confidence: 99%